Nurses’ attitude towards care of dying patient in a teaching hospital - Thapa, Sara; Thulung, Bedantakala; Ghimire, Srijana; Khanal, Dina (Journal of Chitwan Medical College, 2025)
Introduction: Dying is the final portion of the life cycle for all of us which is an inevitable phenomenon. Hence, this study aimed to find out the nurses’ attitudes towards dying patients in a teaching hospital. Method: A cross-sectional descriptive study was conducted among nurses working at Chitwan Medical College Teaching Hospital, Nepal, from 15 Jul 2023 and 15 Aug 2024. Of total 300 nurses, 237 nurses who had six months of work experience in different ward were eligible for the study. From this eligible group, 153 nurses were selected using a simple random sampling method. Ethical approval was obtained prior to data collection. A self-administered questionnaire was used to gather data. The Frommelt Attitude Toward Care of the Dying Scale (FATCOD) was employed to assess nurses’ attitudes toward caring for dying patients. Descriptive statistics (frequency, percentage, measures of central tendency along with measure of dispersion) to summarize data, and inferential statistics of Chi-square tests were used for associations between variables. Result: Out of 153 nurses surveyed, 127(83%) had a positive attitude, and 26(17.0%) had a fair attitude towards care of dying patient. There was statically significant association between the level of attitude towards care of dying patient with current working ward (p=0.048), and training related to care of dying (p=0.046). Conclusion: This study found that majority nurses had positive attitudes towards care of dying patient. Support and continued efforts is necessary to enhance professional development nurses for further improvement in the quality of care of dying patients.